A symbiosis dynamic analysis for collaborative R&D in open innovation. (14th December 2009) - Yang, Chia-Han; Shyu, Joseph Z.
This research aims to propose a symbiosis model for new product development based on the open innovation concept. Particularly, a dynamical model of Lotka-Volterra approach is used to analyse the cooperative R&D relationship between the innovation intermediaries and R&D firms, to share their patent portfolio or resources through open innovation process. The study will develop a symbiosis model to assume the growth rate, growth limitation, and positive interaction effect of both R&D firms and innovation intermediaries, for best discussing the market dynamics in four scenarios. Simple numerical examples will also be adopted to demonstrate the utility of this model.